Self-monitoring adherence to physical activity in children and adolescents with type 1 diabetes - Vanelli, Maurizio; Corchia, Matteo; Iovane, Brunella; Bernardi, Anna; Mele, Alessandra; Chiari, Giovanni (Acta Biomedica Atenei Parmensis, 2006)
Monitoring blood glucose is essential for good diabetes control and even more important when participating in sports.Many variables can have an effect on blood sugar response to aerobic or anaerobic activities. A moderate exercise produces an average fall in plasma glucose of 40% of baseline values.The majority of hypoglycaemia episodes occurs in children with pre-exercise plasma glucose concentrations < 120 mg/dl, therefore it is advisable to achieve a blood glucose level of at least 120 mg/dl if not higher before starting an exercise in order to prevent hypoglycaemia episodes. Since 15 g of oral glucose result in only about a 20-mg/dl rise in glucose concentrations, 30-45 g of oral glucose may be more appropriate to treat hypoglycaemia during exercise. A sufficient adherence to the physical activity prescribed by the health care professionals it easy to find in the children with Type 1 diabetes. According our experience, 60 per cent of the children report to spend on average 1 hour daily for exercise, proving so to consider physical activity beneficial in the treatment of diabetes mellitus. Glycate haemoglobin levels in these motivated patients were better than in children exercising sporadically and shortly either at school or in the spare time. Although the health care professionals effort, only half of the patients referred to monitor blood glucose levels before, after or before and after the exercise. Only one third of the patients reported to regularly adjust insulin dosage to own response to physical activity. Two third of the patients referred to consume added carbohydrate to avoid hypoglycaemia.